2011
DOI: 10.1371/journal.pone.0019114
|View full text |Cite
|
Sign up to set email alerts
|

Nocodazole Treatment Decreases Expression of Pluripotency Markers Nanog and Oct4 in Human Embryonic Stem Cells

Abstract: Nocodazole is a known destabiliser of microtubule dynamics and arrests cell-cycle at the G2/M phase. In the context of the human embryonic stem cell (hESC) it is important to understand how this arrest influences the pluripotency of cells. Here we report for the first time the changes in the expression of transcription markers Nanog and Oct4 as well as SSEA-3 and SSEA-4 in human embryonic cells after their treatment with nocodazole. Multivariate permeabilised-cell flow cytometry was applied for characterising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
(54 reference statements)
2
16
2
Order By: Relevance
“…In untreated hESC, the expression of SSEA-4 is widely acknowledged (most cells express SSEA-4) [33, 34], but as we have shown previously, expression of SSEA-3 correlates more precisely with coexpression of NANOG and OCT4 [33]. Furthermore, by utilising SOX2 detection, two subpopulations of hESC could be characterized: SSEA-3+NANOG+OCT4+SOX2+ cells and SSEA-3+NANOG−OCT4−SOX2+ cells.…”
Section: Discussionmentioning
confidence: 86%
“…In untreated hESC, the expression of SSEA-4 is widely acknowledged (most cells express SSEA-4) [33, 34], but as we have shown previously, expression of SSEA-3 correlates more precisely with coexpression of NANOG and OCT4 [33]. Furthermore, by utilising SOX2 detection, two subpopulations of hESC could be characterized: SSEA-3+NANOG+OCT4+SOX2+ cells and SSEA-3+NANOG−OCT4−SOX2+ cells.…”
Section: Discussionmentioning
confidence: 86%
“…Recent findings [25] corroborate ours on the lengthening of the G 1 phase suppressing hPSC selfrenewal and leading to more extensive differentiation. Hence, controlling, in part, the propensity for commitment through modulation of the cell cycle may be an appealing alternative to growth-arresting agents, such as nocodazole and DMSO, which often induce aberrant differentiation and apoptosis [8,36]. Cells at a low or high density display distinct profiles of the CDK inhibitor p21 (CDKN1A), warranting further investigation into its participation in molecular mechanisms regulating self-renewal or commitment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cycle variability of hPSCs in conditions supporting their self-renewal has received less attention. Interestingly, the fractions of hPSCs in the G 1 phase reported in different studies are not consistent [1,3,[7][8][9]. Considering that cell cycle duration is intimately linked to proliferation kinetics, the wide range of doubling times (T d ; 18 to over 60 h) of hPSCs in many studies [10][11][12] also exemplifies the variability of proliferation and cycle of self-renewing hPSCs.…”
mentioning
confidence: 93%
“…It may also be caused by the arrest itself irrespective of phase or even by direct effect of CDK2 on pluripotency of hESCs [10]. Similar concerns apply to studies which showed that chemical arrest of the cell cycle in G2 using Nocodazole also promotes the differentiation of hESCs [18]. Thus, a causal relation between the G1 phase and differentiation of hESCs has not yet been fully established, and it remains unclear whether hESCs are more sensitive to differentiate in their G1 phase versus other phases.…”
Section: Introductionmentioning
confidence: 86%